An Analysis of Tax Audit Compliance Factors and Model - Saw, Sor-Tin (2019)
This research paper explores the underlying factor structure of a set of observed compliance variables. The purpose is to determine the significant factors in the multidimensional construct. The study was conducted with a sample of 250 service tax licence holders in Malaysia. Compliance data for the three-year audit period are obtained from questionnaires, audit cases and a supporting database. Factor Analysis is conducted to examine the possible variables and validate the number of factors. The results obtained show there is inter-relationship or causal relations existing among the factors of taxpayer compliance; and that the Taxpayer Audit Compliance Construct (TACC) is a 4-factor structure. The Confirmatory Factor Analysis outcomes indicate that ten items load well onto four latent factors, represented by: (1) ‘deficiency claim level, audit outcome’; (2) ‘annual taxable sales, returns submission’; (3)‘penalty on return, number of offence type, nature of offence’; and (4) ‘licence period, auditing experience and age’. Finally the result of this path analysis is validated through the conceptual framework - adapted Fischer et al. (1992) Tax Compliance Model. The TACC Model provides a good fit to the data and can serve as a compliance audit checklist or tool to assist public and private sector organisations in managing risks. The study also contributes to knowledge on taxpayer audits and compliance.